2016
DOI: 10.5194/acp-16-3525-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of observed and modelled aerosol lifetimes using radioactive tracers of opportunity and an ensemble of 19 global models

Abstract: Abstract. Aerosols have important impacts on air quality and climate, but the processes affecting their removal from the atmosphere are not fully understood and are poorly constrained by observations. This makes modelled aerosol lifetimes uncertain. In this study, we make use of an observational constraint on aerosol lifetimes provided by radionuclide measurements and investigate the causes of differences within a set of global models. During the Fukushima Dai-Ichi nuclear power plant accident of March 2011, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 78 publications
5
84
0
Order By: Relevance
“…These wet scavenging developments were also implemented in a GEOS-Chem v9-03-01 simulation of 137 Cs (also using GEOS5 met fields) and evaluated against 137 Cs measurements taken for several weeks following the March 2011 Fukushima Daiichi nuclear power plant accident. Implementation of these scavenging revisions yielded improved agreement with the radionuclide measurements (median ratio of measured to modelled surface-layer concentrations changed from 5.53 to 0.52) and reduced efolding times from 21.8 to 13.2 days, which is close to the measurement value of 14.3 days (Kristiansen et al, 2016). These wet-removal revisions also slightly reduced the mean bias relative to measurements of the number of aerosols larger than 40 nm (N40), 80 nm (N80), and 150 nm (N150) for the same global set of 21 geographically diverse sites as described in D'Andrea et al (2013) (not shown).…”
Section: Simulations and Revisions To Model Parameterizationssupporting
confidence: 58%
“…These wet scavenging developments were also implemented in a GEOS-Chem v9-03-01 simulation of 137 Cs (also using GEOS5 met fields) and evaluated against 137 Cs measurements taken for several weeks following the March 2011 Fukushima Daiichi nuclear power plant accident. Implementation of these scavenging revisions yielded improved agreement with the radionuclide measurements (median ratio of measured to modelled surface-layer concentrations changed from 5.53 to 0.52) and reduced efolding times from 21.8 to 13.2 days, which is close to the measurement value of 14.3 days (Kristiansen et al, 2016). These wet-removal revisions also slightly reduced the mean bias relative to measurements of the number of aerosols larger than 40 nm (N40), 80 nm (N80), and 150 nm (N150) for the same global set of 21 geographically diverse sites as described in D'Andrea et al (2013) (not shown).…”
Section: Simulations and Revisions To Model Parameterizationssupporting
confidence: 58%
“…Aerosols have a lifetime of the order of days (Kristiansen et al, 2016), and the emissions are converted to forcing without an intermediate concentration step.…”
Section: Aerosolsmentioning
confidence: 99%
“…For example, both atmospheric transport models may simulate too short a lifetime of particulate iodine. This, as for many other models, was found for Cs-137 attached to particles after the Fukushima Dai-ichi accident (Kristiansen et al, 2016). The inversion would probably try to compensate a too strong loss of mass by increasing the emitted amount.…”
Section: Discussion Of the Source Termsmentioning
confidence: 86%